Integrated educational environment as a basis of organization of the educational process at the initial school in East Germany - Honcharuk, M. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Problem In the article is explained the integrated educational environment of the initial school in Germany, summarized the experience of organization of educational process at the initial school and described the didactics system of initial school. The author compares task, values and priorities of educational policy in Germany and in Ukraine. Purpose To expose the value of the integrated educational environment of initial school in East Germany; to analyse the tasks and priorities of initial school in the legislative documents of Ukraine and Germany; to characterize the organization of educational process at the initial school of in East Germany; to define conditions of realization of modern educational environment. The Methods used to study General scientific: analysis, synthesis, comparison, classification and generalization, which is necessary for the study of compositions of domestic and foreign researchers, official and normative documents; Structural-functional, which made it possible to outline the organizationally pedagogical conditions of forming the integrated educational environment at the initial school of East Germany and to exposure directions of their realization; comparative, which enabled the definition of possibilities to use of German experience for modernization of organizationally pedagogical support of activity of initial school in Ukraine; empiric methods are conversations, interviews, discussion, consideration of research problems during the meetings with German colleagues and correspondence with the purpose of clarification of practical aspects of activity of initial school. Results In research are exposed the values of integrated educational environment of initial school in East Germany and analyzed the tasks and priorities of initial school in the legislative documents of Ukraine and Germany; described and generalized and experience of organization of the educational process at initial school in East Germany, outlined condition of realization of modern educational environment. Originality For the first time the conditions of forming the integrated educational environment of initial school of East Germany was specified and described the value of educational environment on principles of integration and the experience of organization of educational process at initial school of East Germany. The condition of realization of modern educational environment are outlined; the comparative analysis of some documents is conducted in industry of formation of Germany and Ukraine and it was proved that school education of two these states has a same common goal. Conclusion To generalize the experience of the German researchers is to be emphasized that the forming of the integrated educational environment gives the possibility to find out the problem sides of the school system of education; to find the optimal algorithm of decision of topical questions; to improve the indexes of student's literacy; to promote professionalism of pedagogical staff and smoothing of educational possibilities of students. This experience is extraordinary important for Ukraine and needs to be studied more detailed and to be implemented in the system of domestic primary education.